Rational use of immunosuppressive drugs in vasculitis treatment - Kelleci-Cakir, Burcu; Bayraktar-Ekincioglu, Aygin (Acta Medica, 2025)
Immunosuppressive drugs are essential for the treatment of inflammatory and autoimmune diseases, such as vasculitis. A complete understanding of pharmacological profiles, interaction potentials, and patient-specific variables is necessary for rational drug use. Azathioprine, methotrexate, mycophenolate mofetil, cyclophosphamide and glucocorticoids are common immunosuppressants that have complex pharmacokinetics and are linked to a variety of interactions between drugs, nutrients, and supplements, which may increase the toxicity or change the therapeutic response. Their safety and effectiveness are greatly influenced by metabolic polymorphisms, cytochrome P450 enzymes, and P-glycoprotein transporters. Serious side effects such as nephrotoxicity, myelosuppression, or decreased treatment response might result from inappropriate combinations. Therefore, therapeutic drug monitoring and individualization of therapy by a multidisciplinary approach becomes important. This review emphasizes the importance of rational use of these drugs, patient monitoring and management of drug interactions to ensure safe and effective immunosuppressive therapy, while minimizing preventable risks and maximizing patient outcomes.